Households Socio-Economic Characteristics And The Level Of Accessibility To Water In The Low-Income Areas Of Lagos Metropolis - Fagbohun, P.O.; Ajetomobi, O.O. (Advances in Social Sciences Research Journal, 2018)
The paper assessed socio-economic characteristics of households in the low income area of Lagos Metropolis and the effects on potable water accessibility. Hence, water is central in maintaining good living condition and maintenance of residential building facilities. Such demographic variables that were examined include gender, occupation, education, household size, marital status, income, water facility assets and location. The essence was to establish whether there is relationship between these variables and, quantity and quality used by different households for their domestic activities, such as cooking, drinking, washing, bathing, toileting and general environmental sanitation. Using multistage sampling method, 1,532 households were successfully investigated. Both descriptive and inferential statistical analyses were used, where ANOVA, chi-square and Pearson Correlation Coefficient were employed to test the relationships and effects of some households’ variables on the quantity and quality of water used. The paper discovered that there are relationships between some demographic variables and quantity of water used by households. Both water facilities used and household’s residential location have significant effect on the households’ perceptions on the quality of water they used. It was based on these findings the paper suggested improvement in the socio-economic status, particularly education and income on the need to use adequate quantity and good quality of water. Hence, income status was identified having a significant effect on water consumption capacity to meet the water quantity to be consumed, recommended by WHO and Lagos State, for healthy living and good environmental sanitation. In order to change the perception of households on water quality from the available sources, there is need for the government to ensure water quality control.